Pemikiran Politik Islam Zainal Abidin Ahmad - Fisher Zulkarnain (Universitas Darussalam Gontor, 2017)
Zainal Abidin Ahmad is a prominent Muslim intellectual and political expert from Masyumi who was formed by self-made or self-taught who lived before and after the independence of Indonesia. His ability mastering Arabic, Dutch and English is the most valuable asset so that he is able to master knowledge independently. This makes him in tune with other Masyumi leaders who have formal education graduates. He was also known as the